Diagnostic and therapeutic roles of iron oxide nanoparticles in biomedicine - Chia-Hung Lu; Jong-Kai Hsiao (Tzu-Chi Medical Journal, 2023)
Nanotechnology changed our understanding of physics and chemics and influenced the biomedical field. Iron oxide nanoparticles (IONs) are one of the first emerging biomedical applications of nanotechnology. The IONs are composed of iron oxide core exhibiting magnetism and coated with biocompatible molecules. The small size, strong magnetism, and biocompatibility of IONs facilitate the application of IONs in the medical imaging field. We listed several clinical available IONs including Resovist (Bayer Schering Pharma, Berlin, Germany) and Feridex intravenous (I.V.)/Endorem as magnetic resonance (MR) contrast agents for liver tumor detection. We also illustrated GastroMARK as a gastrointestinal contrast agent for MR imaging. Recently, IONs named Feraheme for treating iron-deficiency anemia have been approved by the Food and Drug Administration. Moreover, tumor ablation by IONs named NanoTherm has also been discussed. In addition to the clinical application, several potential biomedical applications of IONs including cancer-targeting capability by conjugating IONs with cancer-specific ligands, cell trafficking tools, or tumor ablation agents have also been discussed. With the growing awareness of nanotechnology, further application of IONs is still on the horizon that would shed light on biomedicine.